Gina Buijs (ed.): Migrant Women - Crossing Boundaries and Changing Identities - Sørensen, Ninna Nyberg (Tidsskriftet Antropologi, 1994)
Gina Buijs (ed.): Migrant Women - Crossing Boundaries and Changing Identities Anmeldes af Ninna Nyberg Sørensen